Combined 31P and 1H MRS show that impaired muscle O2 supply limits ATP synthesis during exercise in systemic sclerosis - Graham J. Kemp (Clinical Science, 2026)
Abstract Muscle weakness and fatigue feature in many diseases, but the underlying pathophysiology can be difficult to study in vivo. In patients with the chronic autoimmune disease systemic sclerosis (SSc), considerable disability results from small-vessel vasculopathy and progressive fibrosis. Alongside cardiopulmonary limitations on exercise capacity, there is increasing evidence of peripheral dysfunction. In a study reported in this issue, Layec and colleagues investigate this in exercising skeletal muscle in vivo using a combination of phosphorus magnetic resonance spectroscopy (31P MRS) and proton magnetic resonance spectroscopy (1H MRS). The 31P MRS abnormalities (a bigger change in phosphocreatine (PCr) concentration during exercise and slower post-exercise PCr recovery) reflect impaired mitochondrial ATP synthesis, and the larger change in deoxymyoglobin concentration measured by 1H MRS (implying lower myocyte PO2) implicates a defect in O2 supply rather than in mitochondrial O2 use. This major contributor to impaired exercise tolerance would be difficult to establish using classical methods of biopsy and exercise physiology, which shows the power of non-invasive measurement modalities to probe the pathophysiology of complex conditions.